A utilização de leilões em modelos de expansão da rede de transmissão de energia elétrica - Paulo, Goret Pereira (2012)
With the purpose of contributing to the literature about regulation of infrastructure sectors, this paper shows an analysis of the regulatory model used to enable the expansion of the electrical energy transmission capacity in Brazil. In this country, of continental dimensions, the transmission sector plays a vital role enabling the electrical energy supply and, thus, enabling a sustainable growth path for the economic activity. Large amounts of energy are transmitted among generator units, mainly hydroelectric power plants, which, in many cases, are located in regions quite faraway from big consumption centers. Due to the similarity among continental dimensions and volumes of energy produced and consumed, the regulatory models used for the expansion of the transmission in Brazil and Argentina are compared. Institutional and political system aspects in both countries are highlighted in order to explain the differences between the two models as well as the results achieved in each country. In this case, the challenges are highlighted for the expansion of the transmission infrastructure of high tension and large extensions in the Argentinean case, as well as the advantages of the Brazilian model that matches auctioning and a centralized planning mechanism. The peculiarities of the Brazilian regulatory model, mainly concerning the hybrid model of transmission award agreement auctions, along with periodical reviews of investor's revenue, get special attention. Through an analysis of the bids presented in the auctions carried out in Brazil between 2002 and 2008, the reaction of participants is tested as regards the change in the regulatory model introduced in 2006, when the periodical tariff review was introduced in award agreements for transmission services. With this change, participants have not increased the value of their bids at the auctions, indicating that there has not been an increase in the perception of the business risk for investors due to this regulatory change. The information used by the participants to present their bids, in the auction model for transmission expansion in Brazil, is analyzed through an extended sample of the bids presented between 1999-2011. Empirical evidences are found that the participants' bids are correlated, indicating that they take competitors' bids into account in order to elaborate their own bids.